Take your seat at the table : live an authentic life of abundance, wellness, and freedom - ONeal, Anthony; O'Neal, Sam (Nelson Books, an imprint of Thomas Nelson, 2025)
"Are fears and uncertainties keeping you from reaching for your dreams? In Take Your Seat at the Table, bestselling author Anthony O'Neal reveals the indispensable tools and strategies to take ownership of your decisions and step into the life God wants you to live"--